Sustainable aviation technology and operations : research and innovation perspectives - Sabatini, Roberto; Gardi, Alessandro (Aerospace series (Chichester, England), 2024)
"Sustainable Aviation Engineering introduces the key technology enablers and design techniques, as well as the latest regulations and the prominent international programmes, related to the environmental impact and sustainability of aviation. It begins with describing the various pollutants and noise generated during aircraft operations, condensation trails, as well as the governing physical phenomena involved. Mathematical elaboration of the aircraft dynamics and trajectory modelling is included and the mathematical formulation of typical business related aspects is introduced, derived from the operational cost breakdown analysis and including the charges associated to airline flights. Impacts related to the manufacturing and disposal of aircraft and equipment are discussed and innovative aircraft technologies and systems being developed to address the environmental impacts will also be covered. Sustainable Aviation Engineering considers the multi-objective trajectory optimisation problem and provides a set of solution methods for both offline strategic tasks and online tactical real-time implementations. Relevant multi-disciplinary design optimisation methods are described, together with innovative problem resolution techniques. A number of case studies are also included, addressing aircraft design, systems design and mission optimisation for environmentally sustainable aviation."--